Predictors of low birth weight and 24-hour perinatal outcomes at Muhimbili National Hospital in Dar es Salaam, Tanzania: a five-year retrospective analysis of obstetric records - Benjamin Anathory Kamala; Andrew Hans Mgaya; Matilda Michael Ngarina; Hussein Lesio Kidanto (The Pan African Medical Journal, 2018)

(untitled)
INTRODUCTION: The global prevalence of low birth weight (LBW) is 16%, representing more than 20 million infants worldwide, of which 96% are born in low-income countries. This study aimed to determine the prevalence, predictors and perinatal outcomes of LBW newborns. METHODS: We conducted a retrospective analysis of data obtained from the hospital's obstetric and neonatal database. Descriptive statistics and multivariate logistic regression were performed with 95% confidence intervals (CI). RESULTS: The prevalence of LBW was 21% (n = 8,011) and two-thirds of these were delivered at term. Seven percent of newborns were stillbirths and 2% died within 24hrs after birth. Logistic regression revealed that primigravida and grand multiparity were associated with LBW (OR: 1.25, 95%CI: 1.15,1.37; and OR: 1.21, 95%CI: 1.01,1.25, respectively). Having =4 antenatal care (ANC) visits was associated with increased odds of LBW (OR: 1.74, 95%CI: 1.59,1.87). Regression models revealed an independent association between LBW and increased odds of stillbirths (OR = 7.20, 95%CI 6.71,7.90), low Apgar score (OR = 3.42, 95%CI: 3.12,3.76) and early neonatal deaths (OR = 1.82, 95%CI: 1.51,2.19). CONCLUSION: The prevalence of LBW was high and was associated with extreme maternal age groups, grand multiparity, low maternal education, low number of ANC visits and obstetrics risks factors and complications. Both LBW and prematurity were independently associated with poor perinatal outcome. Future interventions should focus on improving the quality of ANC and integrating peripatum emergency obstetric and neonatal care.